Psalm 67 in its literary and ideological context - Botha, Phil J. (Old Testament essays, 2004)
Psalm 67 has been interpreted for a long time as part of an agricultural liturgy of thanksgiving for Yahweh's grace. This paper argues that the psalm's contents, its structure, and its immediate context in the book of Psalms do not justify such an interpretation. It should probably be seen as a call to Yahweh to display and publicly claim his honour, so that all the peoples of the world will recognise Israel's special relationship to him. The strophic structure, poetic features, and ideological intent of the psalm and its neighbours are investigated.